Projeto e implementação de sistema de capacitação em gestão hospitalar: o caso FAE Centro Universitário e Hospital IPO - Kaniak, Vivien Mariane Massaneiro (2014)
The urgent search in contemporary companies for the generation of knowledge as a factor of differentiation creates a growing need for effective mechanisms of cooperation with educational institutions. These institutions, in their role as generators of knowledge also benefit from the interaction with the companies, since their proximity to the reality of the market stimulates the development of both the teaching staff and the students, and promotes innovation as much as visibility of the academy in the community. Within this context, this study aimed to design and implement a training system in hospital management for the Hospital of Otolaryngology of Parana (IPO) in partnership with FAE University Center. Therefore, the present partnership management process of the university were analyzed and compared with the principles of the framework for technology transfer and Company University interaction, the tool proved to be useful mainly to point improvements to the process. Regarding the final product of the cooperation, the MBA in Health Management course, latu sensu, was designed and implemented. This came to meet the demand for training from the hospital. It was also a teaching-learning process solution that became feasible through the cooperation, knowledge exchange, and alignment of interests between partners. We believe that the model described in this study may serve as reference for future partnerships between the university and other companies.